Costs and performance of irrigation projects: A comparison of Sub-Saharan Africa and other developing regions - Inocencio, Arlene B. (Animo Repository, 2007)
High investment costs together with declining world prices for food and the perceived failures of many past irrigation projects are the main reasons for the reluctance of development agencies and governments in sub-Saharan Africa (SSA) to invest more resources in irrigation. This study aims to establish systematically whether costs of irrigation projects in SSA are truly high, determine the factors influencing costs and performance, and recommend cost-reducing and performance-enhancing options to make irrigation investments in SSA more attractive. The study analyzes 314 irrigation projects implemented from 1967 to 2003 in 50 countries in Africa, Asia, and Latin America supported by the World Bank, African Development Bank and the International Fund for Agriculture Development. All data were obtained from Project Completion Reports and Project Performance Audit Reports, complemented with information from Staff Appraisal Reports. This paper makes three important contributions: (1) it confirms some earlier findings and disproves some popularly-held notions and incorrect perceptions about unit costs and performance of irrigation projects in SSA; (2) it provides empirical support to some existing irrigation investment policies and suggests reconsidering others; and (3) it provides some specific recommendations for future irrigation investments. Specifically, the popular view that SSA irrigation projects are expensive has to be understood in its proper context. Using simple regional averages, the unit costs in SSA appear higher than those for other regions. However, a careful look at the details reveals that under certain conditions, unit costs of irrigation projects in sub-Saharan Africa are not statistically different from those in non-SSA regions. Sub-Saharan African projects are not inherently more costly than in other regions. This finding suggests that projects should reflect specific characteristics consistent with lower unit investment costs. In terms of project performance, the regression result indicates that once these specific factors are accounted for, SSA projects can perform significantly better than those in South and Southeast Asia. So, despite the relatively higher failure rate in sub-Saharan Africa, if we carefully take into account the factors influencing performance in project planning, it is possible to formulate better performing projects in the region. The key factors significantly influencing unit irrigation costs include: project size in terms of total irrigated area within a project, average size of irrigation systems within a project, government contribution to investment cost, share of software components in total investment, country’s level of development, design and technology factors (crops irrigated, mode of O&M), and implementation factors (cost overrun and ‘sizing error’). The factors influencing performance of irrigation projects include: project size and average size of systems, complexity of projects as measured by a number of project components, water availability as proxied by annual rainfall and conjunctive use of surface water and groundwater, country’s level of development, farmers’ contribution to investment cost, and design and technology factors. ‘Project size’ is the most important factor determining both unit investment cost and performance of irrigation projects. The larger the ‘project size’, the lower the unit cost and higher the project performance. These results confirm an earlier finding that “big projects just do better than small projects.” At the same time, smaller systems show higher performance, suggesting that big projects supporting small-scale irrigation systems may be best. Irrigation components in multi-sector/sector-wide projects have significant cost-reducing effects despite the relatively smaller irrigated area compared to purely ‘irrigation’ projects. This investment option results in lower unit costs, and points to an opportunity to exploit the economies of scale in big projects even if the area to be irrigated is relatively small and with potentially greater impact on poverty reduction. Projects supporting farmer-managed or jointly-managed (with a government agency) irrigation systems have lower unit investment costs and perform better than projects with systems managed solely by government agency. These results provide empirical evidence to support donor and government policies to enhance farmers’ roles in project formulation, implementation and operation and maintenance. Where farmers contribute to project development, projects perform better than those without farmer contribution. Higher government contribution to total investment costs lowers unit costs, supporting the efficient-government hypothesis, but does not improve economic performance. There is clearly a need to evaluate the type and quality of government intervention to improve impact on performance of projects. Systems designed for horticultural crops have lower unit project cost and higher project performance than those designed for staple food crop production. The major recommendations emerging from the study, addressed to governments and investors in sub-Saharan Africa, are: Under the right conditions, irrigation investments in SSA can provide good returns and have significant impacts on agricultural growth. Therefore, as part of a larger package of investments in support of the CAADP, irrigation investments make sense in many instances. Governments and investors should develop relatively large investment projects irrigating bigger areas, to achieve significant economies of scale. This is not a problem for large countries. To be more effective in assisting smaller countries, regional projects (which may include large countries as well) may offer a way to achieve important economies of scale and synergies among countries as well. There is also a strong case for investing in more water storage in sub-Saharan Africa. Small-scale irrigation schemes offer significant performance advantages over large-scale systems within irrigation investment projects. Therefore, large irrigation investment projects supporting many small-scale irrigation schemes are likely to lead to the best results. Both the software and hardware components of irrigation projects are critical. However, underinvesting in software can lead to significantly higher hardware costs and lower project performance. We recommend investing in good planning, design, project management, and supervision, combined with effective training, capacity building and institutional development among future users and managers. We recommend maximizing farmers’ effective involvement in all stages of irrigation system development and management, from the beginning. Maximizing farmers’ contributions to the development of their systems (consistent with their capacity) combined with farmers taking significant management responsibility for the completed scheme usually results in lower costs and higher performance. We recommend paying very careful attention to the issue of types of crops to be grown. In general, irrigation schemes used only for staple crops are more expensive and have lower performance. Irrigation systems designed for high-value cash crops are cheaper and show higher performance. Wherever conditions are favorable, the design of irrigation schemes should allow for conjunctive use of surface water and groundwater, as it improves performance. This recommendation reinforces the importance of providing a reliable water supply for successful irrigation. We recommend that irrigation be included as a component in multi-sector projects. Regional and collaborative approaches that take advantage of economies of scale in multi-sector projects with irrigation are likely to result in higher performance. However, these projects must be carefully designed to avoid being overly complex, as this does reduce performance. We recommend that donors and governments, under the auspices of NEPAD, sponsor a systematic research program to identify how to optimize the poverty-reduction impacts of irrigation investments in sub-Saharan Africa.